2023
DOI: 10.1002/app.55012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ionic liquids as catalysts on liquid crystal aromatic polyester based on thin‐film polymerization technique

Zexi Wu,
Caijie Shi,
Tao Peng
et al.

Abstract: Liquid crystal aromatic polyesters (LCAPs) have been used in wide applications, such as chip packaging and airship skin. The traditional polymerization of LCAP is catalyzed by inorganic salts, for example, sodium acetate. Herein, we reported three kinds of ionic liquids (ILs) as catalysts to promote LCAP polymerization for the first time. The effects of ILs on the polymerization behaviors are investigated by in situ observing the liquid crystal (LC) phase behaviors based on the thin‐film polymerization techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…■ EXPERIMENTAL SECTION Materials. PAR was synthesized according to previous study in ref 13; its structure formula is shown in Figure S1. ODCB (Macklin, D807178) was purchased from Shanghai Macklin Biochemical Technology Co., Ltd. Potassium hydroxide (KOH) was purchased from Aladdin (Shanghai, China).…”
Section: ■ Introductionmentioning
confidence: 99%
“…■ EXPERIMENTAL SECTION Materials. PAR was synthesized according to previous study in ref 13; its structure formula is shown in Figure S1. ODCB (Macklin, D807178) was purchased from Shanghai Macklin Biochemical Technology Co., Ltd. Potassium hydroxide (KOH) was purchased from Aladdin (Shanghai, China).…”
Section: ■ Introductionmentioning
confidence: 99%